“Medical Men in the New Age”: Alice Bailey’s Impact on Contemporary Energy Healing - Dominic S. Zoehrer (Religions)
Energy healing refers to a globalising market of healing rituals that aim to stimulate the clients’ self-healing process. In the context of healing, the term ‘energy’ has multi-layered meanings and may denote physical, psychological, social, as well as spiritual principles of restoring well-being. This article demonstrates how the idea of energy as a healing agent was embedded within the occult cosmology and anthropology of the British-American post-Theosophist Alice A. Bailey (1880–1949). Applying historical discourse analysis, Bailey’s impact on the emergence of energy healing is examined. Her theory of energy is explored against the backdrop of her esoteric grand narrative. It is demonstrated how Bailey’s principles of energy formed the basis for her vision of a “medicine of the future”. A concluding discussion proves the global influence of Bailey’s ‘energetic turn’ and how it modelled the approach of major holistic actors of the later twentieth century.